Analysis of Coastal Community Health Vulnerability in Facing Climate Change in Coastal Areas in Tapulaga Village, Soropia Subdistrict - Hartati Bahar; Yulinar Rana Rossalina; Andi Abelia; Annisa Nurisati Pratiwi; Augri Aprianingtias; Heni Delfita Maharani; Ulan; Yulinar Rini Rossalina (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Abstract Background: Tapulaga Village, located in Soropia Subdistrict, Konawe District, is a coastal community increasingly facing challenges related to climate change. Environmental sanitation plays a vital role in safeguarding the health and well-being of its residents. This study focuses on assessing the community’s vulnerability to health issues exacerbated by environmental factors, particularly in relation to sanitation, access to clean water, and solid waste management practices. Objective: The primary objective of this study is to evaluate the environmental health conditions of the coastal community in Tapulaga Village and to identify key factors contributing to their vulnerability to the impacts of climate change. Methods: A quantitative analytical method with a cross-sectional design was employed. Data were collected from 200 respondents using structured questionnaires distributed through the Epicollect application. The analysis was conducted using SPSS version 16.0, applying univariate and bivariate techniques to examine the relationships between health vulnerabilities and adaptation measures to climate change. Results: The demographic profile of respondents revealed that the majority were female (53.5%) and within the age group of 31–44 years (36.0%). In terms of sanitation, 90% of households had access to latrines, yet only 36% met the criteria for a healthy home environment. Regarding water access, most residents relied on dug wells; however, 77% of respondents did not boil their drinking water, posing a health risk. In the past six months, 37.5% of respondents reported experiencing illness 1–2 times, with diarrhea being the most prevalent condition. Additionally, respondents expressed significant concern about environmental threats such as coastal erosion and extreme weather events, indicating heightened vulnerability. Conclusion: The overall environmental sanitation conditions in Tapulaga Village are moderately adequate. Nevertheless, areas such as wastewater management and the safety of drinking water remain pressing concerns. Strategic interventions including community-based education and improvements to public health infrastructure are essential to reduce health risks associated with climate change and enhance the resilience of coastal populations. Keywords: Climate Change, Environmental Sanitation, Public Health, Demographic Vulnerability, Coastal Communities, Indonesia